Pathogenicity of three commercial products of entomopathogenic fungi, Beauveria bassiana, Metarhizum anisopilae and Lecanicillium lecanii against adults of olive fly, Bactrocera oleae (Gmelin) (Diptera: Tephritidae) in the laboratory - Mahmoud Farag Mahmoud (Plant Protection Science, 2009)
The pathogenicity of entomopathogenic fungi, Beauveria bassiana, Metarhizum anisopilae and Lecanicillium lecanii, was evaluated against adults of the olive fly Bactrocera oleae (Gmelin) under laboratory conditions by two ways, contact bioassays and oral bioassays. The results showed that oral bioassays caused higher mortality after four treatments than the used contact bioassays. Moreover, the virulence ofL. lecanii was higher than the virulence of B. bassiana and M. anisopilae in both ways of experiment. Lethal time (LT50) was shorter in oral bioassays than in contact bioassays in all treatments. It was 14.67, 8.30 and 5.43 days for B. bassiana, M. anisopilae and L. lecanii with oral treatment while it was 16.6, 26.07 and 12.59 days for B. bassiana, M. anisopilae and L. lecanii, respectively, with contact treatment. The slope values were 2.41, 2.55 and 2.37 for contact bioassays and 1.64, 1.69 and 1.61 for oral bioassays of B. bassiana, M. anisopilaeand L. lecanii, respectively. The mortality response to the interaction between B. bassiana and M. anisopilae was synergistic while the interaction between B. bassiana + L. lecanii and M. anisopilae + L. lecanii showed an antagonistic response.